Evaluation of jet nebulisers for use with gentamicin solution. - Newman, S P (1985)
Recently nebulised antibiotics (gentamicin and carbenicillin) have been used successfully to treat respiratory tract infection in patients with cystic fibrosis. No information exists, however, on the choice of nebuliser or the ideal mode of operation with antibiotic solutions, which are often viscous. The aerosol output, droplet size, and nebulisation time were assessed for four common brands of jet nebuliser (Bird, DeVilbiss, Inspiron, and Upmist) used to nebulise 2 ml (80 mg) and 4 ml (160 mg) of gentamicin solution (Garamycin, Kirby-Warrick) at four compressed gas flow rates (6, 8, 10, and 12 1 . min-1). There were considerable variations between the nebulisers, DeVilbiss and Upmist being most efficient in the release of respirable (less than 5 micron diameter) droplets. Droplet size and nebulisation time were inversely proportional to gas flow rate. Aerosol output and nebulisation time were increased by raising the volume fill from 2 to 4 ml, although nebulisation time could still be restricted to 12 minutes or less with DeVilbiss and Upmist at 12 1 . min-1. The output of drug in droplets of below 5 micron diameter ranged from 7.2 (SE 0.4) to 71.4 (4.3) mg, according to the type of nebuliser, flow rate, and volume fill. These studies suggest that for optimal drug delivery 4 ml gentamicin solution should be nebulised either at a fixed flow rate of 10-12 1 . min-1 or with a high flow compressor. Previous unsatisfactory clinical results with antibiotic aerosols may have been due in part to incorrect choice of nebuliser or inappropriate operating conditions, or both.